2010
DOI: 10.1089/bfm.2010.0003
|View full text |Cite
|
Sign up to set email alerts
|

Nipple Shields: A Review of the Literature

Abstract: Nipple shields have become commonplace in the United States for a wide range of breastfeeding problems. This article is a summary of the current literature describing the evidence for nipple shield use. The authors reviewed all available articles on nipple shields and selected 13 studies for inclusion. The studies were organized into three categories: physiologic responses, premature infants, and mothers' experiences. This review concludes that current published research does not provide evidence for safety or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…Thus, improved social services for single mothers are needed. Our finding on nipple shields is in line with the results of a literature review by McKechnie and Eglash () that concludes that current published research does not provide evidence for the safety or effectiveness of contemporary nipple shield use for either preterm or non‐preterm infants. Feeding less than 10 times per day showed an increased odds ratio by 4.5 for not breastfeeding exclusively.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, improved social services for single mothers are needed. Our finding on nipple shields is in line with the results of a literature review by McKechnie and Eglash () that concludes that current published research does not provide evidence for the safety or effectiveness of contemporary nipple shield use for either preterm or non‐preterm infants. Feeding less than 10 times per day showed an increased odds ratio by 4.5 for not breastfeeding exclusively.…”
Section: Discussionsupporting
confidence: 89%
“…In our own institution, a nipple shield is provided early to mothers in the NICU as a "lactation tool" to preserve mother-infant breastfeeding relation, namely maternal interest in breastfeeding, maintaining lactation, and expressing milk. A number of studies have shown the benefits of the use of nipple shields, although their use has not been readily advocated (17)(18)(19)(20)(21). These studies, however, did not investigate the potential reason or reasons for such advantages.…”
Section: Development Of Suckingmentioning
confidence: 99%
“…Measurements with a Doppler US flow transducer installed in the tip of a latex nipple shield in infants aged 5-9 d showed frequencies under 1 Hz for continuous (i.e., nutritive) suckling and about 2 Hz for intermittent (i.e., nonnutritive) suckling (22). It is obvious that using a latex shield between the nipple and the infant mouth does not represent natural breast-feeding and it has been known to cause disturbances (23). Acquisition of orokinetogram signals in 1-to 2-mo-old infants revealed oral movements at frequencies under 1 Hz during continuous suckling and a band of 4-8 Hz for intermittent suckling (19).…”
Section: Significancementioning
confidence: 99%